2017
DOI: 10.7287/peerj.preprints.3369v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine grained compositional analysis of Port Everglades Inlet microbiome using high throughput DNA sequencing

Abstract: Similar to natural rivers, manmade inlets connect inland runoff to the ocean. Port Everglades Inlet (PEI) is a busy cargo and cruise ship port in South Florida, which can act as a source of pollution and nutrients to surrounding beaches and offshore coral reefs.Understanding the composition and fluctuations of bacterioplankton communities ("microbiomes") in major port inlets is important due to their impacts on surrounding marine environments. We hypothesize annual microbial fluctuations based on seasons (wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Hence, any influence that sea-level (including tides) had on these microbiomes was more likely due to low-frequency variability in currents and/or transports forced by sea-level gradients, rather than to the sea-level variations themselves. In particular, low-frequency variability from both wind setup and tide can drive cross-shelf transport (Castelao et al 2010;Lee & Smith 2002;Leichter et al 1996), affecting microbial connectivity (Sawstrom et al 2016), flushing times (Castelao et al 2010), and the availability of prey and nutrient inputs (Leichter et al 2003;Monismith et al 2010;O'Connell et al 2018). Such effects may serve to reduce microbial alpha-diversity on reefs (O'Connell et al 2018) and may explain the correlations we observed.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, any influence that sea-level (including tides) had on these microbiomes was more likely due to low-frequency variability in currents and/or transports forced by sea-level gradients, rather than to the sea-level variations themselves. In particular, low-frequency variability from both wind setup and tide can drive cross-shelf transport (Castelao et al 2010;Lee & Smith 2002;Leichter et al 1996), affecting microbial connectivity (Sawstrom et al 2016), flushing times (Castelao et al 2010), and the availability of prey and nutrient inputs (Leichter et al 2003;Monismith et al 2010;O'Connell et al 2018). Such effects may serve to reduce microbial alpha-diversity on reefs (O'Connell et al 2018) and may explain the correlations we observed.…”
Section: Discussionmentioning
confidence: 81%